1989
DOI: 10.1177/104063878900100401
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira Abortion in Horses

Abstract: Leptospira infection was diagnosed as the cause of 4 late-term equine abortions/stillbirths and 1 neonatal death in Louisiana. The most consistent gross and microscopic lesions were icterus and interstitial nephritis, respectively. Diagnoses were based on visualization of compatible spirochetes in Warthin-Starry-stained sections of kidney, liver, and placenta. Confirmation by immunofluorescence was made in 2 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0
9

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 6 publications
4
28
0
9
Order By: Relevance
“…27,29,30 In one report, hepatic giant cell formation was thought to be due to leptospiral infection.36 Hepatic lesions such as mixed leukocytic infiltration and hepatocellular dissociation have been reported in equine fetuses as due to leptospirosis. 17,36 The lesions in the kidney seem to be specific for leptospiral infections. Nonsuppurative interstitial nephritis and tubular dilation have been reported in leptospiral infection.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,30 In one report, hepatic giant cell formation was thought to be due to leptospiral infection.36 Hepatic lesions such as mixed leukocytic infiltration and hepatocellular dissociation have been reported in equine fetuses as due to leptospirosis. 17,36 The lesions in the kidney seem to be specific for leptospiral infections. Nonsuppurative interstitial nephritis and tubular dilation have been reported in leptospiral infection.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were not surprising because most of the equine abortion studies reported serogroup Pomona (kennewicki) as a cause of abortion. 3,5,6,9,10,15,16,18 Cases 10 and 32 were confirmed by culture as abortions due to infection by L. interrogans serovar grippotyphosa. A third abortion (case 15) was thought to be a result of infection by leptospires in the Grippotyphosa serogroup because the fetal fluid and dam's serum had titers against grippotyphosa.…”
Section: Discussionmentioning
confidence: 99%
“…La colonización de los túbulos renales proximales de los animales portadores lleva a la eliminación de la bacteria a través de la orina (5). Sin embargo, el hallazgo de ADN por PCR de Leptospira interrogans, serovariedades Bratislava y Pomona, en fluido vaginal de yeguas, sugiere la posibilidad de transmisión sexual (6)(7)(8). Solo se conocen dos registros de detección de ADN por PCR de Leptospira spp.…”
Section: Introductionunclassified
“…en semen de ganado bovino, pequeños rumiantes y porcinos, lo que demuestra una posible transmisión de leptospirosis por contacto sexual (7,8). En equinos, una manifestación común de leptospirosis crónica es la presentación de uveítis recurrente y disminución en el rendimiento atlético; también se presentan fallas reproductivas, abortos debido a la infección intrauterina y muerte fetal (5,11,12), nacidos muertos, mortalidad neonatal y potros débiles al nacimiento (13,11).…”
Section: Introductionunclassified